Cementless long-stem fixation in periprosthetic clamshell fracture: a biomechanical investigation - Zhu, Lingqi; Xie, Li; He, Mingchang; Miao, Jianyun; Zhou, Liang; Huang, Lianshui; Liu, Hui; Xie, Wei; Zhai, Wenliang (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveTo investigate the biomechanical strength of cementless long-stem fixation for the treatment of periprosthetic clamshell fracture.MethodsEighteen Sawbones artificial femur models were used and divided into three groups. Group A had an intact medial wall. Group B, the proximal periprosthetic femoral medial wall was osteotomized to simulate periprosthetic clamshell fractures. Group C, following identical osteotomy to Group B, cerclage wiring was applied to fix the medial wall fracture fragment. After molding, the cementless long-stem were implanted in all models, which were then evaluated through axial compression tests, torsion tests, and axial failure tests. The axial stiffness, axial displacement, torsional stiffness, torque, and maximum failure load were recorded and statistically analyzed.ResultsIn the axial compression tests, no statistically significant differences were observed among Groups A, B, and C in terms of axial displacement, axial stiffness, or maximum failure load (the displacement greater than 3 mm). However, in the torsional tests, Group B showed significantly lower torsional stiffness or torque compared to Groups A and C (p < 0.05). No significant differences in torsional stiffness or torque were detected between Groups A and C.ConclusionThe integrity of the femoral medial wall is crucial for femoral stem stability. In case of medial wall fracture, while cementless long-stem implantation can achieve satisfactory axial stability, its torsional stability remains inadequate. The application of supplemental cerclage wiring for medial wall fragment fixation provides reliable improvement in torsional stability of the stem.